Hospital-to-home care transition program for deep partial-thickness burns: improved scar outcomes and quality of life - Maryam Aliakbari; Sima Zohari Anboohi; Malihe Nasiri; Parvaneh Vasli (Scientific Reports)
Abstract Scar formation, the most common complication of burns, significantly impacts patients’ quality of life. This study evaluates how the hospital-to-home care transition program reduces scar-related complications and improves health-related quality of life in patients with deep partial-thickness burns. This semi-experimental study involved 80 patients with deep partial-thickness burns, selected through convenience sampling and randomly assigned—by coin flipping—to the intervention group (n = 40) or the control group (n = 40). We used the Patient and Observer Scar Assessment Scale and the Burn Specific Health Scale-Brief to assess outcomes. The hospital-to-home care transition program was delivered to the intervention group through three face-to-face educational sessions during discharge from the emergency department and clinic visits, along with two telephone counseling and follow-up sessions in the second and third weeks post-discharge. Data collection occurred at three time points: baseline, the third week after emergency department discharge, and the 12th week post-discharge. We analyzed the data using SPSS v.22 with a significance level set at 0.05. The findings showed that time and group each contributed to reducing scars by 5.71 and 8.81 units, respectively, with an interactive effect of 5.22 units (P < 0.001). Similarly, time and group individually improved health-related quality of life by 21.68 and 26.74 units, respectively, with an interactive improvement of 24.71 units (P < 0.001). The results indicate that the hospital-to-home care transition program helped prevent excessive scar complications and promoted a more favorable scar maturation process, thereby enhancing health-related quality of life in patients with deep partial-thickness burns. Nurses and healthcare planners can apply these findings to improve outcomes for this patient group.